Design of Multimedia Teaching System for Animation Production Based on Virtual Simulation Experiment Platform - Tian, Xiaoxuan; Li, Chengkun (International Conference on Measuring Technology and Mechatronics Automation (Print), 2022)
Because of the incompatibility of animation data format, it is difficult to meet the needs of students in the effect display of animation production. By using the virtual simulation experiment platform to convert the format of animation data, coordinate system and size, to ensure that the system is suitable for different types of animation files and improve the display effect. The test results show that students are satisfied with the display effect and application value of the design system, and the system has been recognized by students.